"Globalna" znanost in konceptualni manko - Vendramin, Valerija (Šolsko polje, 2013)
The concept of intersectionality is taken as a starting point - intersectionality as an interaction between gender and other categories of difference. It is demonstrated that this difference is (yet) again insufficiently theorized, regardless of the declarative feminist acknowledgement that the exclusions played such a distressing role in the formation of the feminist scholarship. Multiple positioning only rarely includes power relations along the East- -West European axis - this "periphering" is not theorised appropriately in hegemonic/hegemonizing Anglo-American feminist theory. This starting point leads furthermore to two issues that play an important part in the legitimization of "science-making" and the formation of the intellectual agenda. The first problem is of a conceptual nature - how universally or culturally marked are the concepts, categories etc. that are used by feminist theory? Secondly, how does the dominance of the certain cultural space and language (English) influence the development of science and the dissemination of scientific results. The existing taxonomies of academic excellence and quality are very much marked by the dominance of some in the scientific community. The article ends with a look at Slovene scientific-research politics - how its conditions and standards "objectively" define good researcher and how it demarcates the possibilities of their scientific work.
Keywords: intersectionality; spol; intersekcionalnost; gender; scientific politics; znanstvena politika; znanstveni dosežki; evaluation of the scientific results; vrednotenje